신규간호사 및 재취업간호사의 재직의도, 현장적응 및 교육요구도 조사 - 김숙정(Sook Jung Kim); 지혜련(Hye Ryeon Ji); 임유진(You Jin Lim); 김남영(Nam Young Kim) (한국콘텐츠학회 논문지, 19(7), 2019)
The purpose of this study is to compare the intention to stay, field adaptation, and educational demands between the new nurses and reemployment nurses. This research was done to create a base for a program that will improve field adaptation, and to prevent dropping out or moving. The followings are the results; There was a significant difference in the intention to stay of the 48 new nurses and 48 reemployment nurses (t = -2.10, p = .038), but there was no significant difference in field adaptation between the two groups (t = -1.48, p = .142 ). Finally, the subjects responded with the topics they would most like to learn about emergency patient care. Through the above results, this study provide basic data for developing a program that can enhance the intention to stay in hospital. 본 연구의 목적은 신규간호사와 재취업간호사의 재직의도, 현장적응 및 교육요구도를 파악하고 비교하는 것이며, 본 연구결과를 통해 현장적응력을 강화하고 이직을 방지할 수 있는 프로그램 개발을 위한 기초자료를 마련하고자 비교조사연구를 방법론으로 적용하였다. 본 연구의 주요내용은 다음과 같다. 연구결과, 간호대학을 졸업한 신규간호사 48명과 6개월 이상의 경력단절기간을 가진 후 재취업한 간호사 48명의 일반적 특성에 따른 재직의도 차이는 결혼에서 유의한 차이가 있었고, 현장적응 정도는 신규간호사의 가족 부양의 책임 유무에서만 유의한 차이가 있었다. 신규간호사와 재취업간호사 두 군간의 재직의도는 유의한 차이를 보였으나(t=-2.10, p=.038), 현장적응은 두 군 간에 유의한 차이를 보이지 않았다(t=-1.48, p=.142). 마지막으로, 연구 대상자들이 가장 원하는 직무교육 주제는 응급환자간호이었다. 이상의 결과를 통해 본 연구는 신규간호사와 재취업간호사의 현장적응을 강화하고 재직의도를 강화할 수 있는 프로그램을 개발하는데 기초자료를 제시하였다.